2022
DOI: 10.3390/su14095530
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to and Strategies for the Climate Village Program Plus: A Lesson Learned from Indonesia

Abstract: The Climate Village Program (CVP) is one of the national flagship programs of the Ministry of Environment and Forestry of the Republic of Indonesia to support emission reduction and climate resilience. This paper examines the challenges and strategies for implementing the climate village program in the national and sub-national contexts. Data and information derived from discussions, seminars, focus group discussions, and interviews with local government officials in East Kalimantan were used to analyze the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The agroforestry pattern is very appropriate to be applied to the forest-land rehabilitation program because it is supported by strong institutions from the community and has a high level of sustainability. According to the existing agroforestry implementations that has been applied in Indonesia as well as other countries, it showed that agroforestry gives an important contribution not only for climate change mitigation [28,29,30,31,32] but also to increase family income, ensure food availability, increase access to financial loans as well as strengthening farmer's institutions at the local level [11,33].…”
Section: The Way Forwardmentioning
confidence: 99%
“…The agroforestry pattern is very appropriate to be applied to the forest-land rehabilitation program because it is supported by strong institutions from the community and has a high level of sustainability. According to the existing agroforestry implementations that has been applied in Indonesia as well as other countries, it showed that agroforestry gives an important contribution not only for climate change mitigation [28,29,30,31,32] but also to increase family income, ensure food availability, increase access to financial loans as well as strengthening farmer's institutions at the local level [11,33].…”
Section: The Way Forwardmentioning
confidence: 99%
“…This program was first launched in 2016, and 3270 villages will have been registered under PROKLIM by 2021 [186]. However, lack of capacity and technical support is still an issue in PROKLIM implementation [199].…”
Section: Adaptation Action Adaptation Roadmapmentioning
confidence: 99%
“…However, it is still necessary to pay attention to the supporting policies and strategies of the parties so that they can support the downstream of NTFPs-based industries. [33,34,35].…”
Section: Green Growth Frameworkmentioning
confidence: 99%